Internet 'changes definition of newspaper' - News Straits, Times (New Straits Times, 2013)
PETALING JAYA: The traditional newspaper must change the way it works to remain relevant to its readers. The New Straits Times Press group managing editor Datuk Abdul Jalil Hamid said the true definition of a traditional newspaper had changed over the years to face the challenges of digital platforms, such as online websites and social media.